Calçadões de cruz alta/RS: uma análise sobre a composição espacial e a qualidade visual da paisagem - Villani, Monique (2023)
The purpose of this study is to analyze the spatial composition and visual quality of the landscape of the pedestrian streets located along Pinheiro Machado Street, in the city of Cruz Alta-RS. These pedestrian zones are located in the central core of the urban area and were built in 1979 and 1980, completely changing the usual morphology of these spaces due to the huge physical intervention and the exclusivity of pedestrian use. These are environments that differ from the usual typology found in the surrounding area and which are found among so many other areas in need of attention, as well as visibility and recognition, due to the historical and social importance they represent. The dissertation is based on a bibliographical review of the context of the urban landscape and the image, these concepts being the basis for the development of the research. Other subjects were also covered, such as the theme of the street, the history of pedestrian zones in Europe, the United States and Brazil, with some examples, as well as the definition of the typologies of these spaces. It also briefly discusses the history of Cruz Alta, the formation of its urban morphology and Pinheiro Machado Street and the construction of the its pedestrian streets, where they were also specialized through maps and photographs. As part of the proposed methodology, images of four points of each pedestrian street were catalogued, in which their structuring elements of the spaces were pointed out. In order to obtain an assessment of their quality, a questionnaire was developed with the general population and with the group of architects and engineers from the Department of Building of Cruz Alta City Hall, to understand the perception of these groups regarding the spatial composition and visual quality of the sites. Finally, these results were triangulated to understand how these components influence the landscape of the Pedestrian Street. Previously, it can be affirmed that the spatial composition of the Calçadões occurs through the combination of different elements arranged in their extensions, coming to compose the landscape, while the evaluation of the visual quality can determine that these elements are agreeable in certain parts of the point of view of the population and others not. Finally, with the general analysis of the results, it is possible to point out some guidelines in proposals for qualification, improvement, and the valorization of these spaces.